UJI AKTIVITAS EKSTRAK ETANOL BIJI PINANG (Areca catechu L.) TERHADAP PENYEMBUHAN LUKA BAKAR PADA KULIT PUNGGUNG MENCIT PUTIH JANTAN (Mus musculus) - Fitri Handayani; Reksi Sundu; Henriko Nober Karapa (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
Areca seeds contain flavonoid, tannin, and alkaloid which can help the healing process of burn wounds on the back skin of mice. Areca seeds are used for treatment because it has antimicrobial activity. Areca Seeds are one of Indonesian plants which the fruit in tranditional way is used as burn medicine. The objective of this study was to know theeffect of ethanol extract of areca seeds against burn wound healing on the back skin of mice. Fifteen mices were used in this experiment and were divided into 5 groups : vaseline flavum as a control negative, branded ointment as a control positive , ethanol extract of areca seeds in vaseline flavum with consentration 20%, 40 % and 60 %. Each group consisted of 3 mices. The back skin of mice was induced using hot iron size 1×1 cm for 2 seconds then given a treatment for 14 days. The percentage of healing of burns by calculating the surface area of wound. The results of its preliminary phytochemical analysis showed the presence of alkaloids, flavonoids, tannins and saponins. The percentage of burn wound healing of ethanol extract in concentration 20 % was 84,33 %, 40 % was 87,67%; and 60% was 89,67%. Data was analyzed using one-way Analysis of Variance (ANOVA) which showed that data has significant differences (P < 0,05) was 0,000. LSD test showed that each treatment group had siginicant differences with significant value < 0,05.